2000
DOI: 10.1007/pl00013660
|View full text |Cite
|
Sign up to set email alerts
|

Electron density modeling and reconstruction of infinite periodic minimal surfaces (IPMS) based phases in lipid-water systems. I. Modeling IPMS-based phases

Abstract: This is the first of two papers dealing with the structural solution of physical systems based on infinite periodic minimal surfaces (IPMS), such as surfactant, lipid-water, and block copolymer systems. In the first paper, the mathematics of minimal surfaces is briefly reviewed and details of the construction of the associate D, P, and G IPMS are described. Electron density models of lipid-water systems based on these IPMS are then constructed. The resulting models are then Fourier transformed to calculate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
59
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 41 publications
8
59
1
Order By: Relevance
“…This observation is in agreement with previously reported data on a different set of PLs (Riccio et al 1986;Haas et al 1998). In order to fit these data, and, first of all, the ones concerning noninteracting PL samples, we first chose to represent each layer as two different slabs with uniform electron density, one related to the alkyl chains and the other one to the polar head groups: this model is well known in the literature and is often used for lipid layers (Kjaer et al 1989;Haas et al 1998;Harper et al 2000;Majewski et al 2001). The relative positions of these head and tail layers give information about the LS film structure: from our analysis of the reflectivity from lipidonly films, this turns out to be a Y-structure, implying a folding of the monolayer during deposition or a recrystallization thereafter, both of which are not uncommon (Schwartz 1997).…”
Section: Multilayerssupporting
confidence: 75%
“…This observation is in agreement with previously reported data on a different set of PLs (Riccio et al 1986;Haas et al 1998). In order to fit these data, and, first of all, the ones concerning noninteracting PL samples, we first chose to represent each layer as two different slabs with uniform electron density, one related to the alkyl chains and the other one to the polar head groups: this model is well known in the literature and is often used for lipid layers (Kjaer et al 1989;Haas et al 1998;Harper et al 2000;Majewski et al 2001). The relative positions of these head and tail layers give information about the LS film structure: from our analysis of the reflectivity from lipidonly films, this turns out to be a Y-structure, implying a folding of the monolayer during deposition or a recrystallization thereafter, both of which are not uncommon (Schwartz 1997).…”
Section: Multilayerssupporting
confidence: 75%
“…The Pn3m cubic phase lattice parameter for RMAD4 is smaller than that for (R/K)-RMAD4, with respective values of 13.3 and 18.2 nm. Because the average negative Gaussian curvature is inversely proportional to the square of the lattice parameter (38), this indicated that the Lys-for-Arg substitutions decreased the amount of negative Gaussian curvature generated by RMAD4. However, the phase behavior of the two peptides was very similar; they both induced negative Gaussian and negative mean curvatures in PE-rich membranes.…”
Section: Resultsmentioning
confidence: 99%
“…The phases and zero crossings of the form factor are determined as described (30,32,38). The electron densities of membrane wall (lipid tails, Ϸ0.30 e/Å 3 ) and water (Ϸ0.33 e/Å 3 ) are known (30,39). The transmembrane domain of PR has a higher electron density than lipid tails (Ϸ0.30 e/Å 3 ) because of the oxygen-and nitrogen-rich amino acids constituting the ␣-helices.…”
Section: Cl-pr Lamellar Superlattice Structures With Controlled Pr 3dmentioning
confidence: 99%
“…The disordered extramembrane loops of PR are assumed to have a much lower electron density. For example, the electron density of flexible hydrocarbon is Ϸ0.16 e/Å 3 (39). The membrane surface has the highest electron density [Ϸ0.46 e/Å 3 (30)], which is easily located by inspection of the (z) map (schematic representation on top of Fig.…”
Section: Cl-pr Lamellar Superlattice Structures With Controlled Pr 3dmentioning
confidence: 99%